Estudio de impacto ambiental en la hacienda Guayacán ubicada en el barrio Guaypira, parroquia Casanga - Jaén Armijos, Tania Marlene (2023)
This research was carried out in the Guayacán farm, which is located in the Guaypira neighborhood in the Casanga parish, in the Paltas canton, in the Loja province. The main production activities in this farm are; corn and peanuts crops and beef cattle raising. Was identified the main environmental and social impacts generated by the development of agricultural activities and cattle raising, for which a baseline survey was carried out through the use of secondary and primary information to characterize the abiotic, biotic and socioeconomic components. Environmental impacts were identified and assessed based on the productive activities carried out during the operation phase at the farm, so that the total of 10 environmental impacts and 3 socioeconomic impacts were established. Subsequently, a quantitative assessment was made by applying the Conesa Fernández-Vítora Importance Matrix, where a positive impact was determined, corresponding to the generation of employment, and 12 negative impacts, of which 2 are critical, 5 are severe and 5 are moderate. Among the critical impacts identified on the farm are the following poor environmental education, which corresponds to the social component, and soil compaction due to cattle overgrazing, which belongs to the environmental component. Finally, based on the information obtained, an environmental management plan was designed, which is made up of 7 programs in accordance with the provisions of the Organic Environmental Code (COA 2019), aimed at the management, conservation and sustainable use of natural resources in the farm. Keywords: agriculture, livestock, environmental impact, socio-economic impact, baseline, environmental management plan.